Answer:
The factored form of 16m²-9 = (4m+3)(4m-3)
Explanation:
16m²-9
To find the factors of the expression, first you have to find out the perfect square of the terms:
4 is the perfect square of 16
∴4 is the number if multiplied two times wil give the product of 16.
m is the perfect square of m²
3 is the perfect square of 9
Then,
16m2-9 = (4m)² - (3)²
Now apply the perfect square formula:
a² - b² = (a+b)(a-b)
Therefore,
(4m)² - (3)² = (4m+3)(4m-3)
Thus the factored form of 16m²-9 = (4m+3)(4m-3) ....